The institutionalization of strategy as a practice in organizational studies (Revista de Administração, 2011)
This paper analyzes the level of institutionalization from the point of view of Strategy as Practice (SAP), resorting to institutional theory as its analytical perspective. Through a bibliographic, bibliometric and sociometric study, the authors analyzed 24 studies published in Brazil and 76 published abroad. The elements analyzed were: number of articles published each year; most cited articles and authors; authors that published the most; cooperation networks among authors and institutions, with the help of UCINET® 6 software; geographic coverage of partnering agreements; and SAP approaches used, through content analysis. The results that stand out are the gap between the first publications in international literature and in Brazil, and the most cited authors (Whittington and Jarzabkowski). The fact that 14 different countries have published articles on SAP indicates geographical dispersion as well as alignment with other approaches. In Brazil, despite the growing number of published articles and the inclusion of SAP as a theme in many events, there is still a lot of room for growth as regards the number of articles, the cooperation networks and the issues researched.